2014
DOI: 10.1111/dar.12182
|View full text |Cite
|
Sign up to set email alerts
|

Personally prescribed psychoactive drugs in overdose deaths among drug abusers: A retrospective register study

Abstract: Personally prescribed PPDs pose a potential threat to people who abuse drugs. Health-care services should invest greater effort in identifying people who abuse drugs and in monitoring their drug prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Previous studies have reported corresponding figures of that in the year before death, a personal prescription was missing in 63% (Hall et al, 2008) and 76% (Rönkä et al, 2015) of fatal overdoses with psychoactive prescription drugs. The slightly lower prevalence in our study may be explained by differences in the study population characteristics (fatally intoxicated vs. living subjects) and in the terminology between the studies.…”
Section: Main Findings and Their Interpretationmentioning
confidence: 80%
See 4 more Smart Citations
“…Previous studies have reported corresponding figures of that in the year before death, a personal prescription was missing in 63% (Hall et al, 2008) and 76% (Rönkä et al, 2015) of fatal overdoses with psychoactive prescription drugs. The slightly lower prevalence in our study may be explained by differences in the study population characteristics (fatally intoxicated vs. living subjects) and in the terminology between the studies.…”
Section: Main Findings and Their Interpretationmentioning
confidence: 80%
“…The slightly lower prevalence in our study may be explained by differences in the study population characteristics (fatally intoxicated vs. living subjects) and in the terminology between the studies. Rönkä et al (2015) included also dispenses of other drugs in the same class (i.e. of opioid analgesics if tramadol was identified).…”
Section: Main Findings and Their Interpretationmentioning
confidence: 99%
See 3 more Smart Citations